3, 3′-Diindolylmethane: A Promising Sensitizer of γ-Irradiation. (22nd October 2015) - Wang, Wenjing; Lv, Maomin; Huangfu, Chaoji; Wang, Fang; Zhang, Jingang
Abstract : Purpose . Radiotherapy is an effective treatment modality in the clinical treatment of breast cancer. The present work investigated the effect of 3, 3′-diindolylmethane (DIM) on γ -irradiation sensitizing human breast carcinoma. Methods . Cell survival, intracellular ROS levels, cell cycle distribution, cell apoptosis, and expression of proteins related to apoptosis were measured with MTT assays, flow cytometry, and Western blot analysis, respectively. Results . In vitro DIM plus γ -irradiation arrested the activity of G2/M phase cell cycle, increased intracellular ROS level, significantly suppressed PARP (poly ADP-ribose polymerase), and enhanced γ -irradiation-induced apoptosis, thereby inhibiting the proliferation of MCF-7 cells. Conclusion . These data provide a rationale for the use of DIM as a promising sensitizer of γ -irradiation.